pitolisant, a novel histamine-3 receptor competitive antagonist, and inverse agonist, in the treatment of excessive daytime sleepiness in adult patients with narcolepsy - Noeen Sarfraz; David Okuampa; Hannah Hansen; Mark Alvarez; Elyse M. Cornett; Juyeon Kakazu; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
Narcolepsy is a debilitating sleep disorder that presents with excessive daytime sleepiness (EDS) and cataplexy, which is a sudden paralysis of muscle tone triggered by strong emotions such as laughing. It is also associated with many other disorders, including psychiatric disorders, neurologic illnesses, and medication side effects. Common causes of delayed and incorrect diagnoses of these conditions include lack of physician familiarity with narcolepsy symptoms and comorbidities which mask narcolepsy signs and symptoms. Current pharmacologic therapies include Modafinil and Armodafinil for EDS and sodium oxybate for cataplexy. This review discusses the epidemiology, pathophysiology, risk factors, presentation, treatment of narcolepsy, and the role of a novel drug, Pitolisant, in the treatment of EDS in adults with narcolepsy. Pitolisant is a histamine-3 receptor (H3R), competitive antagonist, and inverse agonist, acting through the histamine system to regulate wakefulness. It is a novel drug approved in August 2019 by the FDA, is not classified as a controlled substance, and is approved for use in Europe and the United States to treat EDS and cataplexy in narcolepsy. Recent phase II and III trials have shown that Pitolisant helps reduce the ESS score and cataplexy. In summary, based on comparative studies, recent evidence has shown that Pitolisant is non-inferior to Modafinil in the treatment of EDS but superior to Modafinil in reducing cataplexy.